Superconductivity in LaBi3 with AuCu3-type structure. (2nd February 2016) - Kinjo, Tatsuya; Kajino, Saori; Nishio, Taichiro; Kawashima, Kenji; Yanagi, Yousuke; Hase, Izumi; Yanagisawa, Takashi; Ishida, Shigeyuki; Kito, Hijiri; Takeshita, Nao; Oka, Kunihiko; Eisaki, Hiroshi; et al.
Abstract: We succeeded in synthesizing a new intermetallic compound with a AuCu3 -type structure, LaBi3, by utilizing a high-pressure technique. Reacting Bi and LaBi at 450 °C under a pressure of 3.4 GPa resulted in the crystallization of LaBi3 with an a -axis lattice parameter of Sharp superconducting transitions were observed in both its magnetic susceptibility and electrical resistivity at 7.3–7.4 K. The upper critical field and Ginzburg–Landau coherence length ξ 0 were estimated to be 1.70 T and 139 Å, respectively. The superconducting transition temperature T c was found to decrease linearly with increasing applied pressure with a slope of −0.26 K GPa −1 . Band structure calculations indicated that this compound has a multiband nature and that its Fermi energy is located exactly at one of the peak density of states.